Contribution to the study of electrographic in height - De los Ríos, César (1949)
Were studied in 30 electrocardiograms of normal subjects, natives of the height and residents in Huancayo, male and ages ranged from 17 to 27 years: the form, meaning and values ​​of the different waves, segments and intervals, the electrical axis means manifest QRS and T, ventricular gradient, the differential angle rates White-Bock, Sodi-Pallares and Goldberger, the time of onset of the intrinsic deflection in precordial unipolar, time of occurrence of deflection in intrinsicoid standard unipolar leads and members and the electrical position of the heart. The observations are the following sum: 1 wave amplitudes P has half fall within normal but lower than the limits specified in Mexico. (2,400 mts.) Except aVR. 2nd Q wave presents mean amplitudes within normal limits. In aVR has a value that approaches the upper normal limits. 3rd Wave R has mean amplitudes fall within normal but lower than those identified in Mexico and at sea level limits; except aVR where its amplitude is greater. 4th Wave S presents mean amplitudes within normal limits. Variations from the aforementioned sea level and in Mexico, are superior in: DI. DII, DIII, aVL, V4, V5 and V6. Lower in: aVR, VI. V2, V3, and VE. 5th Wave T this mean amplitudes included normal limits but somewhat higher than those reported in Mexico and at sea level, especially in DI. In DIII its value was less than the above. 6th ST Segment presents deflected upward within normal limits in the precordial leads, especially in V2 and V3 (100%) and 1 (97%). Only in two cases and one in V2 V3 came to 3mm. 7th AQRS The average magnitude is less than normal. 8th AQRS The average magnitude is lower when we occupies sextants. 4 and 5 9th AQRS The average magnitude is smaller in the vertical and semi-vertical position in the horizontal. The 10th Middle manifest electrical axis was located AQRS preferably in us. 1 and 6 triaxial reference system of Bayley sextants. A good group ranked No. 5 sexante 11th concordance was observed between the direction of AQRS and electrical position of the heart, corresponding to the right vertical directions of 90 ° and horizontal to the left of 0 °. 12 ° The average magnitude of AT was higher than normal. 13 ° The average magnitude of AT varies depending on their position in the reference system of Bayley triaxal. It was significantly higher when ranked No. 6 sextant, which when placed in the 14 ° N ° 1 The average size of AT is not related to the electrical position of the heart. AT 15 ° preferably held sextant No. 6 16 ° The average magnitude of G was almost the same as that designated as normal. 17 ° The magnitude of G varies depending on its location in the triaxial reference system of Bayley, being considerably greater when sextant ranks No. 6, which when placed in the No. 1 ranked 18 ° G preferably sextant N ° 6 19 ° angle differential was over 60 ° when we held the AQRS. 1, 2, 3 and 4 sextants was less than 60 ° when AQRS We held the sextants. 5 and 6 and the next part of the sextant N ° 1 20 ° rates White-Block, Sodi-Pallares Goldberger and were within normal limits in all cases. 21 ° The time of onset of the intrinsic deflection was in all cases. 22 ° The onset of deflection instrinsecoide was normal in all cases. Horizontal electrical 23 ° position (37%) dominates discreetly vertical (30%). It is located 24 ° 57% of cases with tip rotation back.